Konsep Pemeliharaan Lingkungan pada Kata Bakar dalam Bahasa Dayak di Kalimantan Timur: Kajian Ekolinguistik - Rijal, Syamsul; Hasyim, Muhammad; Lukman, Lukman; Iswary, Ery (ppjbsip, 2023)
One of the ethnic groups that is known for its cultural strength is the Dayak ethnic group, which is widely spread in East Kalimantan Province. The Dayak ethnic group has local wisdom that is synonymous with the forest environment. Almost all of their activities depend on forests, including their source of food. Forest management as agricultural land reflects a uniform cultural process in the Dayak ethnic agricultural system. They use the word burn with nutung vocabulary which is different from burning food, such as pisak, tinuq, and kahang in several Dayak language dialects. This burn vocabulary is seen in 6 Dayak languages in East Kalimantan, namely Dayak Kenyah, Dayak Bahau, Dayak Benuaq, Dayak Tunjung, Dayak Punan, and Dayak Penihing/Aoheng. These six Dayak languages differentiate the word burn for the context of burning land and burning food. Ideologically, these two words are included in the cognitive system of Dayak speakers. Sociologically, they can carry out customary regulations well. Biologically, the use of these two words can maintain the relationship of all flora and fauna in the forest ecosystem. Therefore, these two words are linguistic evidence of the concept of environmental preservation in the Dayak language. AbstrakSalah satu etnis yang terkenal kekentalan budayanya adalah etnis Dayak yang banyak tersebar di Provinsi Kalimantan Timur. Etnis Dayak memiliki kearifan lokal yang identik dengan lingkungan hutan. Hampir semua aktivitas mereka bergantung pada hutan, termasuk sumber lahan pangan mereka. Pengelolaan hutan sebagai lahan pertanian mencerminkan proses budaya yang seragam dalam sistem pertanian etnis Dayak. Mereka menggunakan kata bakar atau membakar dengan kosakata nutung yang berbeda dengan membakar makanan, seperti pisak, tinuq, kahang dalam beberapa dialek bahasa Dayak. Kosakata bakar ini dilihat dari enam bahasa Dayak di Kalimantan Timur, yakni bahasa Dayak Kenyah, Dayak Bahau, Dayak Benuaq, Dayak Tunjung, Dayak Punan, dan Dayak Penihing/Aoheng. Keenam bahasa Dayak ini membedakan kata bakar untuk konteks membakar lahan dan membakar makanan. Secara ideologi, kedua kata ini sudah termasuk dalam sistem kognitif penutur bahasa Dayak. Secara sosiologis, mereka mampu menjalankan regulasi adat dengan baik. Secara biologis, penggunaan kedua kata tersebut dapat menjaga hubungan semua flora dan fauna dalam ekosistem hutan. Oleh karena itu, kedua kata ini menjadi bukti linguistik adanya konsep pemeliharaan lingkungan dalam bahasa Dayak.